Corporate Social Responsibility Actions in Times of Pandemic (Gestão & Regionalidade, 2025)
The article analyzes the social responsibility actions of the largest Brazilian companies during the Covid-19 pandemic. The methodology is characterized as descriptive with a qualitative approach. The documentary method was used to collect data from the corporate website, sustainability report and integrated report of the 30 largest companies in Brazil, selected based on net revenue, according to the positioning in the ranking of the 1000 largest Brazilian companies in 2020. The results indicate that there is a lot of information on social responsibility and sustainability actions, and that projects and programs aimed at social development and philanthropy predominate. Brazilian companies supported society, especially through partnerships with NGOs and the public sector, donation of hygiene and cleaning products, protective equipment and food. The study points out the paths followed by the largest Brazilian companies in the management of social responsibility, contributing to the leverage of socio-environmental practices in private
Keywords: Corporate social responsibility; Sustainability; Pandemic; Covid-19